Analysis of Ankle Foot Design for Transtibial Prosthesis Components using the Finite Element Method - Wahyu Dwi Lestari; Ndaru Adyono (Diponegoro University, 2022)
Finite element method (FEM) has been identified as a tool that can be used to analyze stress and strain behavior occurring in prosthetic components of the lower extremities. The main objective of this study was to analyze the structure of the alternative ankle foot designed for the transtibial prosthesis component. The ankle foot is designed and simulated for strength using Solidworks software. There are two alternative designs of the ankle foot that are designed. The material used is AISI 304 with Young's Modulus 193000 MPa and Poisson's Ratio 0.29. Based on the design results, the lowest weight is owned by alternative design 1 of 491.69 grams. The simulation was carried out under normal running conditions in the midstance phase. The applied load is 1000N. There are three data obtained from the simulation results in the form of von Mises stress, deformation, and strain energy. Based on the simulation results on alternative ankle foot design 2, the value of von Misses stress is lower. Even so, the two alternative designs that have been designed are still within safe limits because they still meet the predetermined safety factor value.